Inflammatory response elicited by Ureaplasma parvum colonization in human cervical epithelial, stromal, and immune cells. Issue 1 (9th December 2021) - Tantengco, Ourlad Alzeus G; Kechichian, Talar; Vincent, Kathleen L; Pyles, Richard B; Medina, Paul Mark B; Menon, Ramkumar
Abstract : Ureaplasma parvum is a commensal bacterium in the female reproductive tract but has been associated with pregnancy complications such as preterm prelabor rupture of membranes and preterm birth (PTB). However, the pathologic effects of U. parvum in the cervix, which prevents ascending infections during pregnancy, are still poorly understood. To determine the impact of U. parvum on the cervix, ectocervical (ecto) and endocervical (endo) epithelial and stromal cells were incubated with U. parvum . Macrophages were also tested as a proxy for cervical macrophages to determine the antigenicity of U. parvum . The effects of U. parvum, including influence on cell cycle and cell death, antimicrobial peptide (AMP) production, epithelial-to-mesenchymal transition (EMT), and inflammatory cytokine levels, were assessed. U. parvum colonized cervical epithelial and stromal cells 4 h post-infection. Like uninfected control, U. parvum neither inhibited cell cycle progression and nor caused cell death in cervical epithelial and stromal cells. U. parvum increased the production of the AMPs cathelicidin and human β-defensin 3 and exhibited weak signs of EMT evidenced by decreased cytokeratin 18 and increased vimentin expression in cervical epithelial cells. U. parvum induced a proinflammatory environment (cytokines) and increased MMP-9 in cervical epithelial cells but promoted pro- and anti-inflammatory response in cervical stromal cells and macrophages. U. parvum may colonize the cervical epithelial layer, but induction of AMPs and anti-inflammatory response may protect the cervix and may prevent ascending infections that can cause PTB. These findings suggest that U. parvum is a weak inducer of inflammation in the cervix.